HLA antigens expressed on murine cells are preferentially recognized by murine cytotoxic T cells in the context of the H-2 major histocompatibility complex. - Holterman, M J (1986)
The frequency of murine cytotoxic T lymphocytes (CTL) capable of responding to HLA antigens expressed on human or murine cells was determined by limiting dilution analysis. HLA antigens expressed on human cells stimulated CTL with a precursor frequency of about 1 in 2 X 10(5) spleen cells in primed mice, over two orders of magnitude weaker than a primary allogeneic response. There was a 10-fold increase in the frequency of precursors responding to HLA antigens when they were expressed on murine cells. It was determined that the increased frequency of responders was due to CTL that could only recognize HLA antigens on the syngeneic murine line to which they had been stimulated and that these CTL could not lyse any other HLA expressing murine cells of different H-2 haplotypes. The lytic activity of these CTL was inhibited by H-2b-specific antibodies. These results indicate that such CTL recognize HLA antigens in the context of the H-2 major histocompatibility complex. The magnitude and specificity of CTL responses to xenoantigens are discussed in the context of a model for T-cell interactions with major histocompatibility antigens.